Outcome following scapulothoracic and glenohumeral joint exercise rehabilitation for an elite gymnast with shoulder subacromial impingement syndrome - Gilbertson, M. j. (Journal of Australian Strength and Conditioning, 2019)
Strength and conditioning coaches can play a crucial role in driving the exercise approach for treatment of subacromial impingement syndrome (SAIS) and can substantially reduce the economic burden of funding what could be unnecessary or unsubstantiated surgical interventions for this condition.